Uma avaliação qualitativa da presença de micotoxinas e micro-organismos toxigênicos em insumos e em cervejas artesanais - Paix, Murilo D`Abruzzo (2019)
Consisting primarily of water, hops, malted and non-malted cereals as well as yeast, beer is one of the most consumed alcoholic fermented beverages in the world. Although there are risk laws that compromise product quality, some pathogens such as fungi can contaminate the raw material used in beer production with secondary metabolites. For example, mycotoxins which are compounds produced by filamentous fungi, which in certain amounts can cause disease in animals and humans. Thus, we studied some fungi of the species of the genus Fusarium spp. and Aspergillus flavus to identify which mycotoxins could produce when grown in vitro under favorable input conditions (barley, maize and rice) used by microbreweries for the production of craft beers. These microorganisms when cultivated under favorable conditions, it was possible to find in their fungal extract that fungi of the genus Fusarium spp., Produced mycotoxins such as Zearalenone, α-Zearalenol and β-Zearalenol, Nivalenol, Fumonisin B1, in relation to the extract. obtained from the cultivation of the fungus Aspergillus flavus, it was possible to observe the production of mycotoxin Aflatoxin B1. Six craft beers were produced on a laboratory scale using the same previous inputs without contamination with the fungi in different proportions of barley, corn and rice, in which these samples when subjected to liquid chromatography coupled with mass spectrometry, but were not found. In addition, a study was carried out under which fungi could be isolated from barley grains used by microbreweries, where it was possible to isolate seven fungi. And with micro-cultivation and MALDI-TOF experiments, two fungi may belong to the genus Fusarium sp. and the genus Mucor sp.. Several bacteria were also found when isolating microorganisms, which were also submitted to experiments using MALDI-TOF, many of which have a very similar proteomic profile.